The Seasonality of Market Integration : The Case of Indonesia's Stock Markets - Shieldvie, Halim; Brahmana, Rayenda; Aldrin, Herwany (LPEM, 2011)
Even though Market Integration and the weekend effect have been extensively investigated in the oast two decades, the examination of its linkage has been rarely found. Considering its importance for portfolio practices, this study investiagtes the possibility of integration to occur on a certain day over the period of january 2000 until December 2010. This research employed Stehle's (1977) ICAPM model for measuring the weekend effect in rolling regression mode. To control the equation, we introduce the exchange rate of IDR-to-USD, and oil prices. For robustness, we adopetd and modified the FRench's Model to examine the seasonality inside market integration. This research remarks that there is seasonality in stock market integration.